2021
DOI: 10.1111/ijcp.14652
|View full text |Cite
|
Sign up to set email alerts
|

The knowledge of community pharmacists about appropriate dosing of antibiotics among paediatrics: A national study from Jordan

Abstract: Objective Paediatric patients are highly exposed to medication errors especially dosing errors. This study assessed the community pharmacists' knowledge about appropriate dosing of antibiotics among paediatric patients, factors affecting community pharmacists' knowledge and barriers that lead to inappropriate dosing of antibiotics. Methods A self‐administered questionnaire was distributed to 1283 Jordanian pharmacists who worked in community pharmacies. Descriptive statistics and multivariate regression were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
1
4
1
1
Order By: Relevance
“…Thus, this proved that the students had poor knowledge regarding the dose of salbutamol in paediatric as most of them could answer question 6 correctly while for question 3 most of them answered wrongly once the dose was not given in the question. For question 8, in contrast to the study by Keewan et al, most of the students answered wrongly the question that involved Augmentin® dose calculation [9]. This could be due to the question design, which differs from the current study.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Thus, this proved that the students had poor knowledge regarding the dose of salbutamol in paediatric as most of them could answer question 6 correctly while for question 3 most of them answered wrongly once the dose was not given in the question. For question 8, in contrast to the study by Keewan et al, most of the students answered wrongly the question that involved Augmentin® dose calculation [9]. This could be due to the question design, which differs from the current study.…”
Section: Discussioncontrasting
confidence: 86%
“…Assuring healthcare professionals can appropriately calculate drug doses is vital in preventing a drug-related adverse event [ 8 ]. A pharmacist who is responsible for ensuring the safety and efficacy of medicines that will be consumed by patients, especially children, adequate knowledge of drug dosing calculation should be ensured, as it has been reported that poor knowledge of drug dosing calculation may be one of the factors contributing to inappropriate medicine dosing [ 1 , 9 ]. When choosing dosage, mass, volume, or amount, it is critical to utilise the correct calculating procedures [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the weight of the child was written in the prescription, despite that only 10 (4%) CPs identified the wrong dose and recalculated the dose based on the weight and age of the child. This result was low compared to the study conducted in Jordan which assessed the knowledge of community pharmacists about appropriate dosing of antibiotics among pediatrics, where about 29% of CPs determined the correct dose of Co-amoxiclav in otitis media [ 34 ]. Furthermore, a higher result was observed in another study that aimed to measure the awareness and knowledge of Palestinian Pharmacists about pediatric doses using a questionnaire, where (51.7%) of the pharmacists gave the correct answer for the dose of Co-amoxiclav [ 35 ].…”
Section: Discussionmentioning
confidence: 81%
“…Some pharmacists may also lack knowledge on how to dose co-trimoxazole based on weight. A questionnaire conducted to evaluate the knowledge of community pharmacists about appropriate dosing of antibiotics in pediatrics showed that 84% of pharmacists did not dose co-trimoxazole correctly in pediatrics, which is also dosed based on weight [14]. Another study found that co-trimoxazole was more often underdosed in comparison with other antibiotics in pediatrics [15].…”
Section: Discussionmentioning
confidence: 99%